The Social Services : The immediate problem and the way forward (London : The Socialist Medical Assocation)
1944 1944 1940s 34 pages of strikes, and the employer's obvious reply was the threat of the sack. Under war conditions, instead of merely making the demands for changes the workers have to show why they are necessary and how improvements can be effected, and they have also to help to carry them out, usually in co-operation with management and welfare officers. Thus factory welfare has advanced from being something the management provided only when it seemed profitable to do so (or to comply with legislation) to being the collective responsibility of workers and employers. The work of meeting the needs and solving the problems of people in their capacity as producers has not been universally regarded as a social service, and industrial welfare workers and labour managers are not agreed as to whether they should be called social workers. If these services are provided solely by employers, it is correct to say they are not 'social' services, but the general trend of opinion is that they should move towards being social services, provided by the government, just as medical officers in industry should be paid by the State and not be the management. The Ministry of Labour has had a gigantic job in supplying labour to all essential industries and ensuring for this purpose that every person was employed to the best advantage. The intention has been to place workers in the jobs most suited to their training and ability. An attempt has been 26 15X/2/464/1